Wood engineering and construction handbook. (New York : McGraw Hill, 1997)
Wood properties; Preliminary design considerations; Columns; Bending members; Mechanical fasteners and connectors; Trusses; Structural wood panels; Diaphragms and shearwalls; Arches and domes; Miscellaneous wood structures; Wood foundation structures; Adhesives.
Includes bibliographical references and index.
Keywords: Buildings; Wooden; Building, wooden